Implementation of Virtual Fiber Optic Module Using Virtual Reality for Vocational Telecommunications Students - Sukaridhoto, Sritrusta; Fajrianti, Evianita Dewi; Haz, Amma Liesvarastranta; Budiarti, Rizqi Putri Nourma; Agustien, Lusiana (JOIV : International Journal on Informatics Visualization, 2023)
Virtual Reality (VR) technology is a computer technology capable of replicating a real environment into an immersive world. VR is also capable of simulating the user's physical condition so that they are able to interact. In the world of education as a support for educational activities, especially for vocational high school students who are more dominant in practicum, this study aims to show the results of the early stages of implementing Fiber Optic (FO) learning support modules. The module development process is carried out in several stages: scenario preparation, 3D asset development with low poly optimization, scenario integration with 3D assets, triggering every interaction, multiuser settings, and implementation. To build a good VR Fiber Optic application, measurements using OVR metrics are carried out. This measurement aims to determine the reliability of the application that affects the user experience. In the OVR metric measurement, the highest FPS value is 43, and the lowest FPS value is 27. The value obtained is good enough to run VR applications with low poly asset composition. Measurement of the level of user satisfaction is also carried out by using the PIECES Framework. From the measurement results, the value of each variable is in the range of 3.4 - 4.91, which means that users are satisfied with the VR FO application as a virtual learning support module. This research shows that Virtual Reality technology can provide an overview of practicum that is easy to access and not limited by space and material.